Approach to the production of serious games and adapted elements for teaching science and biology to deaf students - Barbosa, Jesildo Nascimento; Nogueira, Gisele (The ESPecialist, 2024)
Teaching Science and Biology to deaf students requires overcoming challenges to ensure equitable access to scientific knowledge. Therefore, the creation of accessible teaching materials, combined with stimulation, critical thinking and active participation is essential for teaching to be enriching. The main objective of this review was to discuss the effectiveness of serious games, present in the adapted materials, in promoting the learning of Science and Biology by deaf students. The review brings a compilation of research aimed at practical and transformative instructions in the inclusive educational area, with a view to teaching Science and Biology.